Development of an online course for caregivers of older stroke patients - Débora Francisco do Canto; Francine Melo da Costa; Lediane Raquel Woiciechoski; Ana Luísa Petersen Cogo; Lisiane Manganelli Girardi Paskulin (Revista Gaúcha de Enfermagem, 2023)
ABSTRACT Objective: To describe the development process of a massive, open, and online course for family caregivers of older people who had a medically diagnosed stroke. Method: Experience report on the development of a massive, open, and online course. The preparation of the course took place from July 2021 to October 2022 and consisted of the stages:definition and analysis of the contents of the course; construction and approval of the storyboard; digital construction and approval of the early version; making the project available on a digital platform; preliminary evaluation and approval of the final version. Results: The course aims to provide tools for the family care of older people who have suffered a stroke, improving their ability to provide care. It was built in twelve modules, using demonstrative videos, hypertext, pictures, and narrations. Conclusion: The course development process required a team with expertise in different areas and had a positive preliminary assessment.